Some Biochemical properties of polyphenoloxidase from spearmint (Mentha arvensis) - Neves, Valdir Augusto [UNESP]; Picchi, Douglas Gatte [UNESP]; Silva, Maraiza Aparecida da [UNESP] (Brazilian Archives of Biology and Technology, 2009)
Polifenoloxidase (PPO, EC 1.14.18.1) extraída de folhas de Mentha arvensis foi isolada por precipitação com (NH4)2SO4 e diálise extensiva. Seu pH e temperatura ótimos variaram com o substrato. A PPO apresentou atividade com vários difenóis. Valores de Km foram 0,825; 0,928 e 7,41 mM para ácido caféico, 4-metilcatecol e catecol, respectivamente. Na inativação térmica, 50% da enzima foi inativada após 60 e 15 segundos a 70 e 75ºC, respectivamente. A medida de atividade residual mostrou um efeito estabilizante de sacarose a várias temperaturas e uma energia de ativação (Ea) para inativação aumentando com a concentração de sacarose de 0 a 40% (p/p). Valores de energias de ativação de 78,13; 80,37; 82,79 and 81,00 kJ/Mol foram encontradas para 0, 15, 30 e 40% de sacarose, respectivamente. A PPO foi inibida pelos ácidos ascórbico, benzóico, cinamico, ferulico, p-cumárico, protocatéquico, além de metabisulfito de sódio, resorcinol e pirogalol. Os valores de Ki mostram que o ácido ascórbico foi o mais efetivo inibidor. O tipo de inibição foi determinado para cada inibidor.

Polyphenoloxidase (PPO; EC 1.14.18.1) extracted from Mentha arvensis leaves was isolated by (NH4)2SO4 precipitation and extensive dialysis. Its optimum pH and temperature varied with the substrate. The PPO showed activity with various diphenols. Km values were found 0.825, 0.928 and 7.41mM for caffeic acid, 4-methylcatechol and catechol, respectively. on heat-inactivation, half of the activity was lost after 60 and 15 sec at 70 and 75ºC, respectively. Measuring of residual activity showed a stabilizing effect of sucrose at various temperatures with activation energy (Ea) for inactivation increasing with sucrose concentration from 0 to 40% (w/w). Ea values of 78.13; 80.37; 82.79 and 81.00 kJ/Mol were found for 0, 15; 30 and 40% sucrose, respectively. PPO was inhibited by ascorbic, benzoic, cinnamic, ferulic, p-coumaric, protocatechuich acids, sodium metabisulfite, pyrogallol and resorcinol. The Ki values showed that ascorbic acid was the most effective inhibitor. The type inhibition was determined for each inhibitor.
Keywords: polyphenoloxidase; Mentha arvensis; characterization; heat inactivation; inhibitors